Treatment of male stress urinary incontinence with the adjustable transobturator male system: Outcomes of a multi‐center Iberian study. Issue 4 (9th January 2018) - Angulo, Javier C.; Cruz, Francisco; Esquinas, Cristina; Arance, Ignacio; Manso, Margarida; Rodríguez, Andrés; Pereira, Javier; Ojea, Antonio; Carballo, Manuel; Rabassa, Miguel; Teyrouz, Antoine; Escribano, Gregorio; et al.
Abstract : Aim: To evaluate effectiveness and safety of the adjustable transobturator male system (ATOMS) for male stress urinary incontinence (SUI). Material and Methods: A retrospective multicenter study was conducted in nine Iberian institutions using a board‐approved database for 215 patients intervened between 2012 and 2017, with no case excluded. Continence status, patient satisfaction, number, and grade of complications (Clavien‐Dindo) and factors affecting dry rate at adjustment were evaluated. Multivariate analysis defined the population at best success rate. Incontinence recurrence due to device failure and/or explant was evaluated and Kaplan‐Meier curve for durability performed. Results: Adjustment was achieved at a mean 1.4 ± 1.9 fillings. Dry‐rate after adjustment was 80.5% (96.2% mild and 75.3% moderate‐severe), 121 (56.3%) used no pads, and 52 (24.2%) a security pad with urine loss under 10 mL. Mean basal daily pad‐test and pad‐count decreased from 484 ± 372.3 mL and 3.9 ± 2 pads to 63.5 ± 201.2 mL and 0.9 ± 1.5pads (both P  < 0.0001). Satisfaction rate was 85.1% (94.3% mild and 82.1% moderate‐severe). Factors associated to dryness were: lesser severity of SUI ( P  < .0001), absence of radiotherapy ( P  = 0.0002) and device generation ( P  = 0.05). Multivariate analysis revealed absence of radiation (OR = 3.12; 1.36‐7.19), mild (OR = 19.61; 3.95‐100), and moderate (OR = 2.48; 1.1‐5.59) SUI were independent predictors. Complications presented in 33(15.35%); 66.7% grade 1, 9.1% grade 2, and 24.2% grade 3. At 24.3 ± 15 mo mean follow‐up device was explanted in seven (3.25%) and SUI worsened after adjustment in nine (4.2%). Dry‐rate at follow‐up was 73% and durability of device in dry patients at adjustment was 89.8% (82.9‐94) at 2‐years. Conclusions: This study confirms ATOMS device is safe and achieves high treatment efficacy and patient satisfaction in a multicenter setting. Significantly better results are achieved in less severe and non‐irradiated cases. Durability of the device is reassuring in the short‐term.